From Endoderm to Progenitors: An Update on the Early Steps of Thyroid Morphogenesis in the Zebrafish - Marelli, Federica; Rurale, Giuditta; Persani, Luca (Frontiers in Endocrinology, 2021)
The mechanisms underlying thyroid gland development have a central interest in biology and this review is aimed to provide an update on the recent advancements on the early steps of thyroid differentiation that were obtained in the zebrafish, because this teleost fish revealed to be a suitable organism to study the early developmental stages. Physiologically, the thyroid precursors fate is delineated by the appearance among the endoderm cells of the foregut of a restricted cell population expressing specific transcription factors, including pax2a, nkx2.4b, and hhex. The committed thyroid primordium first appears as a thickening of the pharyngeal floor of the anterior endoderm, that subsequently detaches from the floor and migrates to its final location where it gives rise to the thyroid hormone-producing follicles. At variance with mammalian models, thyroid precursor differentiation in zebrafish occurs early during the developmental process before the dislocation to the eutopic positioning of thyroid follicles. Several pathways have been implicated in these early events and nowadays there is evidence of a complex crosstalk between intrinsic (coming from the endoderm and thyroid precursors) and extrinsic factors (coming from surrounding tissues, as the cardiac mesoderm) whose organization in time and space is probably required for the proper thyroid development. In particular, Notch, Shh, Fgf, Bmp, and Wnt signaling seems to be required for the commitment of endodermal cells to a thyroid fate at specific developmental windows of zebrafish embryo. Here, we summarize the recent findings produced in the various zebrafish experimental models with the aim to define a comprehensive picture of such complicated puzzle.